Application of Topical Autologous Platelet-Rich Plasma for Treatment of Pemphigus Foliaceus Wounds: A Case Report - Nopriyati; M. Akip Riyan Saputra; Yulia Farida Yahya; Sarah Diba (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Pemphigus foliaceus (PF) includes lesions on the skin, generally without involving the mucosa. Wounds in PF arise on the outer layer of the superficial skin, but if left untreated, the wound will not heal and will multiply. Platelet-rich plasma (PRP) containing a variety of different growth factors can be used in wound care. This study was at a time to describe autologous PRP therapy in the treatment of excoriated erosional wounds in patients with pemphigus foliaceus. Case presentation: A woman, 35 years old, married, a housewife living in suburban, comes to the emergency department with complaints of blisters accompanied by pain in the face, body, and back which has been increasing since 1 month ago. Examination of the skin showed palpebral blisters on the eyelids of the left and right eyes. In the anterior and posterior trunk regions, proximal 1/3rd and suprapubic extremities, there are hyperpigmented erythematous macules, multiple, nummular-plaque, discrete, partially confluent, with white to brownish scales, single layer and exfoliative. In the posterior trunk region, Nikolsky's sign was positive. Laboratory evaluation showed an increase in leukocytes and neutrophils. ANA examination showed negative results and anti-ds-DNA 54.91. Management of pemphigus in the form of topical and systemic treatment. Topical management in the form of an open compress with 0.9% NaCl solution, Intrasite gel®, and closed Cutimed sorbact® for erosion and excoriation. Topical PRP was administered on the 7th day of treatment. On the 14th day after treatment with topical PRP, the patient is allowed to go home with the repair of lesions throughout the region. Conclusion: PRP therapy in cases of pemphigus foliaceus is very useful in improving the clinical condition of the patient.